Expansions in clinical nursing practice. - Nelouise Geyer (AOSIS, 1997)
In this article some expansions to which nurses are exposed in clinical nursing practice, are highlighted. Opsomming Enkele uitbreidings in die kliniese verpleegpraktyk in Suid-Afrika waaraan verpleegkundiges blootgestel is in die kliniese praktyk, word in hierdie artikel uitgelig. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.